Synchronizing Geomagnetic Field Intensity Records in the Levant Between the 23rd and 15th Centuries BCE: Chronological and Methodological Implications. (7th December 2020) - Shaar, Ron; Bechar, Shlomit; Finkelstein, Israel; Gallet, Yves; Martin, Mario A. S.; Ebert, Yael; Keinan, Jonathan; Gonen, Lilach
Abstract: Archeomagnetic records are an important source of information on the past behavior of the geomagnetic field. Frequently, however, coeval archeomagnetic intensity (archeointensity) datasets from nearby locations display significant discrepancies, hampering precise reconstruction of high‐resolution secular variation curve. This is the case for the time interval between the later phase of the Early Bronze and the early phase of the Late Bronze Ages (23rd–15th centuries BCE) in the Levant and Mesopotamia. We address the problem by cross‐correlating archeointensity datasets from four major multilayered archeological sites in the southern Levant (Hazor and Megiddo), northern Levant (Ebla), and western Upper Mesopotamia (Mari). We report new archeointensity data, obtained using the Thellier‐IZZI‐MagIC and the Triaxe methods, from six strata at Hazor and four radiocarbon‐dated strata at Megiddo. From 39 pottery fragments, 199 specimens passed our selection criteria, from which we calculated the mean archeointensity for each stratum. To strengthen the comparison of these data with previously published data from Mari and Ebla, obtained using the Triaxe method, we conducted a blind test of the methods that resulted in indistinguishable results or a difference of less than 1 μT. The synchronized compilation, constrained by radiocarbon data from Megiddo, displays a V‐shaped pattern with a prominent minimum of at least 200 years centered around the 18th century BCE. The study highlights the importance of stacking archeomagnetic data obtained by different archeointensity methods only after cross‐testing the methods and ensuring that archeological samples were dated in a consistent manner. Plain Language Summary: Archeological materials heated to high temperatures, such as pottery, can act as recorders of the ancient geomagnetic field and may provide invaluable information on its behavior through time. With the advance of paleomagnetic techniques, geophysicists can recover, with greater precision than ever, the absolute intensity of the geomagnetic field at the time when an archeological artifact was heated. However, archeological uncertainty often hampers the possibility of precisely dating these materials. This poses a challenge to both archeologists and paleomagnetists. In this paper, we demonstrate a cross‐disciplinary collaboration which sheds light on fundamental problems regarding the Ancient Near East in the Bronze Age. The underlying principle of the method is that contemporaneous ceramics from nearby archeological sites must have recorded the same field intensity. We use this approach to synchronize archeomagnetic intensity records of four major Bronze Age sites in the Levant and Mesopotamia: Hazor, Megiddo, Ebla, and Mari. We tie the combined record to radiocarbon ages from five strata at Megiddo. The intensity‐synchronized compilation depicts fast changes in the ancient field intensity, which illuminates some long‐standing chronological disputes regarding the history of the Ancient Near East. Key Points: Archeointensity compilation of the Levant and western Upper Mesopotamia based on synchronized datasets from Mari, Ebla, Hazor, and Megiddo Compatibility of paleointensity data was verified through a blind test of the Triaxe versus the Thellier‐IZZI‐MagIC methods Synchronization of the archeological timescale was achieved by linking the data to radiocarbon ages from Megiddo